2D Transition Metal Dichalcogenides for Photocatalysis - Yang, Ruijie; Fan, Yingying; Zhang, Yuefeng; Mei, Liang; Zhu, Rongshu; Qin, Jiaqian; Hu, Jinguang; Chen, Zhangxing; Hau Ng, Yun; Voiry, Damien; Li, Shuang; Lu, Qingye; et al. (Angewandte Chemie International Edition, 2023)
Two‐dimensional (2D) transition metal dichalcogenides (TMDs), a rising star in the post‐graphene era, are fundamentally and technologically intriguing for photocatalysis. Their extraordinary electronic, optical, and chemical properties endow them as promising materials for effectively harvesting light and catalyzing the redox reaction in photocatalysis. Here, we present a tutorial‐style review of the field of 2D TMDs for photocatalysis to educate researchers (especially the new‐comers), which begins with a brief introduction of the fundamentals of 2D TMDs and photocatalysis along with the synthesis of this type of material, then look deeply into the merits of 2D TMDs as co‐catalysts and active photocatalysts, followed by an overview of the challenges and corresponding strategies of 2D TMDs for photocatalysis, and finally look ahead this topic. The fundamentals of 2D transition metal dichalcogenides (TMDs), their synthesis, their advantages in photocatalysis, and the strategies for boosting their photocatalytic performance are summarized in this review. Current problems and their solutions are presented.